Tinjauan Hukum Pidana Atas Pengalihan Laba Melalui Transfer Pricing Sebagai Mekanisme Penghindaran Pajak di Indonesia - Rossa Putri Juliana; Supanto Supanto; Riska Andi Fitriono (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Taxes are mandatory levies imposed on citizens to be used as public investment to boost the country's economic growth. However, Indonesia is estimated to experience tax losses of US$601 per year due to tax avoidance. One of the most commonly used schemes is profit shifting through transfer pricing. The author using normative juridical research method will answer about how the general scheme of profit shifting using transfer pricing method and how effective the current tax laws and regulations work to overcome the problem.